Community Participation in school Management in Ghana - ARYEH-ADJEI, ABIGAIL (Journal of Interdisciplinary Studies in Education, 2021)
It is widely recognized by community members that the participation of the community in school management promotes a sense of community ownership and student learning. This paper is a literature review on community participation in Ghanaian schools. The scope of this paper include  the importance of community participation in school management, the context of school management in Ghana as well as the challenges of community participation in school management. It is recommended that Ghanaian parents and other stakeholders should be encouraged to participate fully in the schools to promote development in the education sector and in the entire community.